Factors influencing unethical behaviour in banking industry - Analisa, Analisa (Journal of Contemporary Accounting, 2020)
This study adopts GONE (Greed, Opportunity, Need, Exposure), the Dark Triad and Fraud Pentagon theories to examine the influences of stress, narcissism, arrogance, greed and work environment on unethical behaviour in the banking industry in Special Region of Yogyakarta, Indonesia. The purposive sampling technique is used to recruit 97 respondents. The PLS-SEM (Partial Least Square-Structural Equation Modelling) analysis shows that stress, narcissism, and greed positively and significantly influence unethical behaviour. Arrogance does not influence positively and significantly unethical behaviour. However, there is a positive and significant relation between arrogance and unethical behaviour in the work environment. This study only used unethical behaviour as an indicator. Further research should experiment on other different indicators and also add intention as an intervening variable.